Microbiome in prostate cancer: pathogenic mechanisms, multi-omics diagnostics, and synergistic therapies - Chengran Wang; Tianqi Dong; Xin’ao Rong; Yuce Yang; Jianhui Mou; Jiaqi Li; Jianli Ge; Xupeng Mu; Jinlan Jiang (Journal of Cancer Research and Clinical Oncology)
Abstract Background Prostate cancer (PCa) is a leading cause of cancer-related deaths in men, with the microbiome emerging as a significant factor in its development and progression. Understanding the microbiome's role could provide new insights into PCa pathogenesis and treatment. Objective This review aims to explore the interactions between the microbiome and PCa, focusing on microbial imbalances and their effects on immune responses, inflammation, and hormone levels. It also discusses advanced research techniques and the potential for microbiome modulation in PCa management. Methods The review synthesizes current literature on the microbiome’s role in PCa, highlighting differences in microbial composition between cancerous and healthy prostate tissues. It examines techniques such as high-throughput sequencing and metagenomics and explores the mechanisms through which the microbiome influences PCa. Conclusions The review reveals substantial microbial differences in prostate tissues of PCa patients compared to healthy individuals, indicating a potential link between microbiome alterations and disease progression. It highlights the promise of microbiome-based strategies for diagnosis and treatment and underscores the need for further research into personalized, microbiome-centric approaches for PCa management.